2021
DOI: 10.3390/jfmk6040093
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Effects of L-Carnitine Supplementation on Physical Performance in Healthy Subjects, the Key to Success in Rehabilitation: A Systematic Review and Meta-Analysis from the Rehabilitation Point of View

Abstract: L-carnitine supplementation improves body strength, sports endurance and exercise capacity, as well as delaying the onset of fatigue. The aim of this study was to identify the correct dosage of supplementation to obtain improvements in physical performance and evaluate the changes related to L-carnitine supplementation in specific metabolic parameters, such as serum lactate, VO2, serum total and free carnitine at rest and after physical activities, in healthy subjects. The search was conducted on PubMed, EMBAS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
3
0
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 55 publications
2
3
0
4
Order By: Relevance
“…Previous studies have shown that L‐carnitine supplementation reduces the lactate concentration in the plasma of athletes after exercise 37,38 . In addition, 3 weeks of L‐carnitine supplementation has the effect of reducing lactate levels in the plasma of humans 39 . In the present study, L‐carnitine treated ewes had lower levels of lactate in the plasma compared to controls at 120 and 150 days of gestation.…”
Section: Discussionsupporting
confidence: 57%
See 1 more Smart Citation
“…Previous studies have shown that L‐carnitine supplementation reduces the lactate concentration in the plasma of athletes after exercise 37,38 . In addition, 3 weeks of L‐carnitine supplementation has the effect of reducing lactate levels in the plasma of humans 39 . In the present study, L‐carnitine treated ewes had lower levels of lactate in the plasma compared to controls at 120 and 150 days of gestation.…”
Section: Discussionsupporting
confidence: 57%
“…37,38 In addition, 3 weeks of L-carnitine supplementation has the effect of reducing lactate levels in the plasma of humans. 39 In the present study, L-carnitine treated ewes had lower levels of lactate in the plasma compared to controls at 120 and 150 days of gestation. However, kids born to L-carnitinetreated ewes had higher levels of lactate in plasma after the cold challenge.…”
Section: Discussionsupporting
confidence: 45%
“…Consequently, micronutrients and natural compounds, commonly known as nutraceuticals, should be included in the regimen to prevent or mitigate exerciseinduced oxidative stress and associated symptoms. For instance, supplementation with Lcarnitine enhances body strength, sports endurance and exercise capacity, while delaying the onset of fatigue, a typical symptom related to cancer that hinders adherence to rehabilitation and physical exercise [47]. Therefore, specific strategies for alleviating constipation should be integrated into a broader project aimed at improving overall health in patients with cancer.…”
Section: Discussionmentioning
confidence: 99%
“…18,19 Additionally, investigations have shown decreased L-carnitine levels in people with PCOS and strong connections between lower L-carnitine levels and an increased risk of developing hyperinsulinemia in patients with PCOS. [20][21][22][23] Moreover, experimental studies have shown that adding L-carnitine can improve ovarian dysfunction in PCOS, which is linked to its antioxidant activity. Based on these data, one can suggest, to explain the improved biochemical and clinical pregnancy rates in the current study, that L-carnitine, through its anti oxidative activity, has resulted in the prevention of apoptosis and this may improve the ovarian environment and oocyte quality in addition to improved endometrial environment and process of implantation; however, the exact molecular mechanisms needs further experimental research work to be elucidated.…”
Section: Discussionmentioning
confidence: 99%